NDVI Analysis And Land Use Change To Support New Rice Field Development Plans In Central Lampung Regency - Ardianto, Asep; Zakaria, Wan Abbas; Murniati, Ktut; Abidin, Zainal; Asmara, Sandi (Universitas Galuh, 2025)
As an effort by the Indonesian government to meet domestic rice production, in 2016 the government through BBWS Mesuji Sekampung planned the development of new rice fields covering an area of more than 17,000 ha in Central Lampung Regency. The development of new rice fields must be supported by the availability of water by building the Way Sekampung Dam, but until the dam is inaugurated in 2021, the development of new rice fields has not been implemented. This study aims to analyze vegetation density and land use at the location of the new rice field development plan. This study uses a quantitative approach with a spatial analysis method. The analysis uses NDVI methods and guided classification to create land use classifications, using Sentinel 2 satellite imagery from 2017 to 2024. Based on the results of the NDVI analysis, it can be explained that there was a considerable change in vegetation in October 2023, due to a rainfall anomaly with a category below normal. Meanwhile, changes in land cover from 2017 to 2023 occurred quite large in the classification class of paddy/field and other vegetation. The increase in paddy field/field land cover from 89.00% to 92.88% was due to the reduction of other vegetation cover such as large vegetation/rubber tree fields (10.37% to 6.21%). Meanwhile, the increase in built-up land is still in the low category of 42 ha.